Numerical investigation on the effect of balcony open and solid upstand on smoke contamination in atrium balconies - Mutafi M.A.; Nasif M.S.; Pao W.; Ismail F.B. (Institute of Physics Publishing, 2023)
Computational fluid dynamics; Computer software; Contamination; CFD simulations; Fire dynamic simulators; Flowthrough; Numerical investigations; Smoke